Role Stress, Kompensasi Finansial, Motivasi Kerja dan Kepuasan Kerja - Riska Wulandari; Ida Bagus Teddy Prianthara (Universitas Pendidikan Nasional, 2018)
ABSTRACTThe purpose of this study is to determine the effect of role stress, financial compensation and work motivation on job satisfaction. This research was conducted at Rural Bank in Denpasar. The population in this research is all employees of BPR in Denpasar City. The sampling technique used accidental sampling obtained on 80 samples used in this research. The results of this study indicate that there is a negative and significant influence between role stress on work motivation. The existence of positive and significant influence between financial compensation to motivation work is a negative and significant influence between role stress and job satisfaction. The existence of positive and significant influence of financial compensation on job satisfaction. The existence of positive and significant influence between work motivation on job satisfaction. The value of direct influence is greater than the value of indirect influence this means that the motivation variable does not mediate the influence of role stress on job satisfaction. The value of direct influence is greater than the value of indirect influence this means that the motivation variable does not mediate the influence of role stress on job satisfaction. For the company should know what factors that influence the achievement of job satisfaction. Based on the results of financial compensation research and work motivation positively affect the job satisfaction, should provide compensation in accordance with what is done by employees / employees. This will trigger employee motivation to work better again in the future. When sufficient financial compensation and the achievement of a good work motivation will suppress the role of stress that is owned by employees, the situation will lead to good employee satisfaction.